Impact of Prophylactic Use of PEG-rhG-CSF on First-Line Immunochemotherapy in Advanced NSCLC: A Cohort Study - Li Sun, MD; Yuan Tian, MD; Shuling Zhang, MD, PhD; Letian Huang, MD; Jietao Ma, MD, PhD; Chengbo Han, MD, PhD (JTO Clinical and Research Reports)
Introduction: This study aimed to assess the impact of prophylactic use of PEG-rhG-CSF on first-line immunochemotherapy in advanced NSCLC. Methods: A cohort of patients with advanced NSCLC who received first-line immunochemotherapy at Shengjing Hospital of China Medical University between January 2019 and July 2024 was selected for this study. Patients were divided into the following two groups: a treatment group that received prophylactic PEG-rhG-CSF (≥1 cycle) 48 hours after immunochemotherapy and a control group that did not receive PEG-rhG-CSF. The primary end points were progression-free survival (PFS), overall survival (OS), overall response rate, and safety. A propensity score-matched analysis was performed to reduce potential confounders. Results: A total of 220 patients were enrolled, with 87 in the treatment group and 133 in the control group. Median PFS was 10.5 months in both the treatment and control groups (p = 0.86), and median OS was 33.9 months in the treatment group versus not reached in the control group (p = 0.71). The overall response rate was 64.4% in the treatment group and 58.6% in the control group (p = 0.40). After propensity score-matched analysis (each group included 78 patients), median PFS was 12.6 months in the treatment group versus 10.5 months in the control group (p = 0.99), and median OS remained 30.3 months in the treatment group versus not reached in the control group (p = 0.85). The treatment group had a reduced incidence of chemotherapy interruptions, any grade of leukopenia, any grade of neutropenia, and grades 3 to 5 neutropenia, without an increase in immune-related adverse events. Conclusions: The prophylactic use of PEG-rhG-CSF in patients with advanced NSCLC undergoing first-line immunochemotherapy did not compromise efficacy and safety. It reduced chemotherapy interruptions and neutropenia, without increasing immune-related adverse events, thus supporting safe and uninterrupted treatment.